7‐ketocholesterol‐induced caspase‐mediated apoptosis in Saccharomyces cerevisiae. Issue 8 (3rd October 2013) - Yue, Qiulin; Zhou, Xiuhong; Leng, Qianli; Zhang, Lele; Cheng, Beijiu; Zhang, Xin
Abstract The cytotoxicity of cholesterol oxidation products has been documented in several mammalian cell lines. It can lead to a wide range of diseases. However, the molecular mechanisms underlying this toxicity in vivo are scarce. The objective of the present study was to assess the potential toxic effects of 7‐ketocholesterol, an important cholesterol oxidation product, on Saccharomyces cerevisiae. Our data show for the first time that 7‐ketocholesterol can induce dose‐dependent cell death in S. cerevisiae. These results suggest that the death induced by this compound is apoptotic and accompanied by chromatin condensation, the production of ROS, and translocation of phosphatidylserine from the inner to the outer leaflet of the cytoplasmic membrane. We further showed that 7‐ketocholesterol‐induced cell death was partially rescued after pretreatment with caspase inhibitor (Z‐VAD‐fmk). In addition, caspase deletion resulted in promotion of cell viability. All these results strongly indicated that 7‐ketocholesterol induces apoptosis in yeast cells through a caspase‐dependent pathway.